2017
DOI: 10.1038/s41467-017-02221-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain insulin resistance impairs hippocampal synaptic plasticity and memory by increasing GluA1 palmitoylation through FoxO3a

Abstract: High-fat diet (HFD) and metabolic diseases cause detrimental effects on hippocampal synaptic plasticity, learning, and memory through molecular mechanisms still poorly understood. Here, we demonstrate that HFD increases palmitic acid deposition in the hippocampus and induces hippocampal insulin resistance leading to FoxO3a-mediated overexpression of the palmitoyltransferase zDHHC3. The excess of palmitic acid along with higher zDHHC3 levels causes hyper-palmitoylation of AMPA glutamate receptor subunit GluA1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
150
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(173 citation statements)
references
References 58 publications
(57 reference statements)
6
150
0
Order By: Relevance
“…Under the pathological condition, the increased PAT activity may promote the effect of 2‐BP. Thus, it has been reported that 2‐BP reverts GluA1 hyper‐palmitoylation in the rats treated by high‐fat diet or cocaine exposure . Different from 2‐BP, the direct de‐palmitoylation by NtBuHA is not dependent on PATs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Under the pathological condition, the increased PAT activity may promote the effect of 2‐BP. Thus, it has been reported that 2‐BP reverts GluA1 hyper‐palmitoylation in the rats treated by high‐fat diet or cocaine exposure . Different from 2‐BP, the direct de‐palmitoylation by NtBuHA is not dependent on PATs.…”
Section: Discussionmentioning
confidence: 98%
“…Many evidence indicates that aberrant palmitoylation signaling leads to pathology . Thus, pharmacological inhibition of palmitoylation may be potentially used as in the treatment of diseases associated with aberrant palmitoylation signaling, such as human cancer, INCL, brain insulin resistance, and cocaine addiction As a hydroxylamine derivative that mimics palmitoyl‐protein thioesterase, the unique medical value of NtBuHA is to treat INCL (Batten disease), a devastating neurodegenerative lysosomal storage disease caused by mutations in the gene encoding palmitoyl‐protein thioesterase‐1. Here, we observed that palmitoylation‐deficient state initiated by NtBuHA preferentially inhibited AMPAR function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin signalling has also been shown to contribute to synaptogenesis and synaptic remodeling in the rat brain and cultured hippocampal neurons [59], two mechanisms essential for neuronal plasticity. Recently, an interesting study has shown that brain insulin-resistance induced by high-fat diet impairs memory and underlying synaptic plasticity through hyperpalmitoylation of AMPA glutamate receptor subunit GluA1 [60], indicating that intact insulin signalling is required for memory formation. Besides experimental models, in humans, intranasal insulin has been shown to improve memory functions in healthy subjects [61, 62], with no effect on word recall and non-declarative memory but rather on declarative, hippocampus-dependent memory contents [62, 63].…”
Section: Central Insulin Signalling: Impact On Cognition and Metabolismmentioning
confidence: 99%